The Effects of Youth Employment: Evidence from New York City Lotteries. (26th September 2015) - Gelber, Alexander; Isen, Adam; Kessler, Judd B.
Abstract: Programs to encourage labor market activity among youth, including public employment programs and wage subsidies like the Work Opportunity Tax Credit, can be supported by three broad rationales. They may (i) provide contemporaneous income support to participants; (ii) encourage work experience that improves future employment and/or educational outcomes of participants; and/or (iii) keep participants "out of trouble." We study randomized lotteries for access to the New York City (NYC) Summer Youth Employment Program (SYEP), the largest summer youth employment program in the United States, by merging SYEP administrative data on 294, 100 lottery participants to IRS data on the universe of U.S. tax records; to New York State administrative incarceration data; and to NYC administrative cause of death data. In assessing the three rationales, we find that (i) SYEP participation causes average earnings and the probability of employment to increase in the year of program participation, with modest contemporaneous crowdout of other earnings and employment; (ii) SYEP participation causes a modest decrease in average earnings for three years following the program and has no impact on college enrollment; and (iii) SYEP participation decreases the probability of incarceration and decreases the probability of mortality, which has important and potentially pivotal implications for analyzing the net benefits of the program.